Histórias e memórias institucionais a partir do acervo fotográfico do Centro Universitário Franciscano (1955-1980) - Brito, Luciana Souza de (2010)
This paper presents the study about the Centro Universitário Franciscano´s stories and memories, which can be caught through the analysis of the photographic collection of the institution. The general objective of this work consists on the treatment according to the criteria archival photographic of the Centro Universitário Franciscano, referring to the period between the years 1955 and 1980 with the aim to study and recall the stories and memories of the institution. As specific objectives, are listed the following activities: to do the diagnosis of the acquis and the physical conditions of the images, the lifting of the documentary volume; to do the hygienic process and pack the collection according to the archival criteria and finally to study the histories and institutional memories from the analysis of the photographic selected series. The work is structured as follows: the first chapter discusses conceptual issues about the central themes of work: stories and institutional memories and cultural heritage. The second chapter presents a detailed study of the producer institution of photographic collection and its supporting institution, since its creation in Heythusen the Netherlands, until it s arrive in Brazil and consequently in Santa Maria. Chapter three deals with the haracterization of the photographic collection of the institution, in which activities were developed for the diagnosis and management of the collection, with activities related to hygiene, identification, organization and packaging. The last chapter covers the analysis of the photographic collection, through the use of the methodology proposed by Boris Kossoy for the construction of a photographic narrative, and that consists of the central focus of the work. So, the work is finished with the final considerations of the author and the reference used.